Spatial, social cognition and team performance - Mumtaz Muhammad Khan; Suleman Aziz Lodhi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
The team members' interaction with the environment and with the members helps shape their spatial, social cognitions respectively. These cognitions help in formulating an understanding of mental models necessary for team performance. At the theoretical level, the relation between spatial, social cognitions and team performance is becoming an exciting field, as it allows not only the investigation of important aspects of spatial and social cognition, but also its relation to team performance. At the empirical level, this line of research covers a vast and varied range of tasks, measures, and effects, as properly demonstrated by this contribution, through experimental research design. The results show that Spatial and Social Cognitions have individually and collectively positive significant impact on team performance.
Keywords: 330; spatial; social cognition; team mental model; team performance; understanding